2003
DOI: 10.1080/0042098032000106636
|View full text |Cite
|
Sign up to set email alerts
|

Zero Tolerance for the Industrial Past and Other Threats: Policing and Urban Entrepreneurialism in Britain and Germany

Abstract: Recent years have witnessed changes in the discourses and practices of urban policing towards 'quality-of-life offences' and the presence of unwanted groups (beggars, drug-users) in city centres. The authors argue that the change towards a more 'law-and-order' style of law enforcement, often referred to as Zero Tolerance Policing, has to be examined not solely as a means of crime prevention but also in the context of interurban competition. Thus, it constitutes a moment of the urban political economy, often re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 30 publications
0
62
0
12
Order By: Relevance
“…The literature on revanchism and the missing attention to politics While Smith referred specifically to New York, and other scholars concentrated on the North American context (Slater 2004, Wyly andHammel 2005), discussions on revanchism have been also empirically grounded in Britain (McLeod 2002, Macleod and Ward 2002, Atkinson 2003, Western Europe (Belina andHelms 2003, Uitermark andDuyvendak 2008), South America (Swanson 2007), and India (Whitehead and More 2007), in relation to public space, policing, the housing market and welfare retrenchment.…”
Section: Research Questions and Methodologymentioning
confidence: 99%
“…The literature on revanchism and the missing attention to politics While Smith referred specifically to New York, and other scholars concentrated on the North American context (Slater 2004, Wyly andHammel 2005), discussions on revanchism have been also empirically grounded in Britain (McLeod 2002, Macleod and Ward 2002, Atkinson 2003, Western Europe (Belina andHelms 2003, Uitermark andDuyvendak 2008), South America (Swanson 2007), and India (Whitehead and More 2007), in relation to public space, policing, the housing market and welfare retrenchment.…”
Section: Research Questions and Methodologymentioning
confidence: 99%
“…(MacLeod, 2002, p. 605) In contradiction with a rhetoric of social mix, diversity and inclusion, a number of authors have demonstrated that the physical and economic renaissance of urban spaces is often accompanied by new forms of social control that can actually stimulate processes of exclusion and marginalization (MacLeod, 2002;MacLeod & Ward, 2002;Holden & Iveson, 2003;Lees, 2003;Raco, 2003c;Johnstone, 2004;Coaffee, 2005). Before New Labour came into power, there was already evidence that the (Labour-led) 'entrepreneurial' urban regeneration politics of various city councils had been accompanied by new practices of redesigning, reordering and controlling public spaces (MacLeod, 2002, andBelina &Helms, 2003, on Glasgow). More recently, however, it has been stressed that the promoted visions of the 'urban idyll' and the 'good city' often exclude those groups perceived as a threat or those who cannot participate, i.e.…”
Section: The Control and Sanitizing Of Public Space In The Renaissancmentioning
confidence: 99%
“…The concern for 'safer cities' became a central theme in the course of the reinvention of cities and interurban competition in the 1980s and 1990s (Taylor et.al.1996, Taylor 1997, Belina and Helms 2003, and the preoccupation over safety played a major role in shaping a response to black cultural forms. In addition, while capital investments into residential developments in the city centre have certainly accentuated the role of the night-time economy in the city's transformation in the 1990s, it is the often-underestimated role of a local critical infrastructure and their cultural capital that shall be emphasized here.…”
Section: Cultural Change and Criminalisationmentioning
confidence: 99%
“…The concern for 'safer cities' became a central theme in the course of the reinvention of cities and interurban competition in the 1980s and 1990s (Taylor 1997, Belina andHelms 2003), and the preoccupation over safety played a major role in shaping a response particularly to black cultural forms.…”
Section: Cultural Change and Criminalisationmentioning
confidence: 99%